Bilateral stroke: unpaired anterior cerebral artery infarct rare presentation - Vidyasagar, Kekathi; Bai, Sandhyapogu Lakshmi; Venkataswamy, P.; Chandrasekhar, S.; Sameeraja, Vaddera; Reddy, Ravikaladhar (International Journal of Research in Medical Sciences, 2017)
ACA territory is an uncommon site for occlusive vascular strokes. Small degree of asymmetry of anterior arteries is present in 80% of patients. Common variants of anterior cerebral arteries include aplasia or hypoplasia of A1 segment. Hypoplasia is found in 10% and aplasia in 1-2% of postmortem examinations. Of all ischemic strokes ACA territory strokes constitutes only 0.6 to 3%. Bilateral ischemic stroke in unpaired ACA is rare entity. We report a case of unpaired ACA due to hypoplasia of right ACA, presenting as stuttering hemiplegia with bilateral focal neurological deficit.